From nature to clinic: Quercetin’s role in breast cancer immunomodulation - Fang, Liguang; Gao, Dandan; Wang, Tong; Zhao, Haijun; Zhang, Yanan; Wang, Shijun (Frontiers in Immunology, 2024)
Immunotherapy has brought hope to many breast cancer patients, but not all patients benefit from it. Quercetin (Qu), a natural product found in various sources, has anti-inflammatory and anti-tumor properties. We conducted a review of the pharmacological research of Qu in regulating anti-tumor immunity in vivo and in vitro. Qu can directly regulate the local tumor microenvironment (TME) by enhancing the activity of immune cells which includes promoting the infiltration of T cells and natural killer (NK) cells, inhibiting the recruitment of myeloid-derived suppressor cells and tumor-associated macrophages. Additionally, Qu inhibits anaerobic glycolysis in tumor cells, thereby reducing the production and transport of lactic acid. It also suppresses tumor angiogenesis by targeting the vascular endothelial growth factor (VEGF) pathway and the vitamin D pathway. Furthermore, Qu can enhance the efficacy of immunotherapy for breast cancer by modulating the systemic microenvironment. This includes inhibiting obesity-related chronic inflammation to decrease the production of inflammatory factors, regulating the composition of intestinal microbiota, and intervening in the metabolism of intestinal flora. At the same time, we also address challenges in the clinical application of Qu, such as low absorption rates and unknown effective doses. In conclusion, we highlight Qu as a natural immunomodulator that enhances immune cell activity and has the potential to be developed as an adjunct for breast cancer.